IMPLEMENTATION OF RISK MANAGEMENT OF KSPPS IKS BOGOR CITY TO SUPPRESS NPF - Suretno, Sujian; Hasyim, Hasnil (Khidmatul Ummah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Financing risk is one of the risks that occurs in financial institutions, especially Sharia cooperatives. Financing risks must be minimized and managed professionally for the business to continue and perform well. Several Islamic cooperatives experienced collapse or went out of business, one of which was due to the high Non-Performing Financing (NPF) reaching above 5%. The negative impact of a high level of non-performing financing is a low level of collection, which will directly result in low income or business profits. For this reason, it is necessary to carry out good risk management by implementing several preventive solutions after a financing failure.